Correction: Timing of surgery in acute deep partial-thickness burns: A study protocol. - Roos F C Salemans; Denise van Uden; Margriet E van Baar; Tjitske M Haanstra; Carine H M van Schie; Paul P M van Zuijlen; Ymke Lucas; Sonja M H J Scholten-Jaegers; Annebeth Meij-de Vries; Fiona M Wood; Dale W Edgar; Inge Spronk; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0299809.].